Comparison of Similes and Metaphors in Translations (In Act of Beneficent Knowledge) - Jasurbek Tulkinjon Ugli, Ibragimov; Fariza Tuxtabayevna, Kholdarova; Shehrozbek Tulkinjon Ugli, Ibragimov (International Journal of Psychosocial Rehabilitation, 2020)
During the last century a great deal of work has been done in the study of the poem Yusuf Has Hajib's "Kutadgu Bilig," which was the first Turkic manuscript. In Uzbekistan, Professor Kayum Karimov did some research on translating this work in Uzbek and presented it in a language that is understandable to readers. Working on a scientific article, three versions were analyzed and studied. Their bytes were compared. As a result, every translation has some differences, but we can see the similarity between the translations, especially in translations by May and Ivanov. Because, separately, Walter May has translated this work from a Russian translation from Ivanov.